The Effectiveness of Integrated Microteaching Lesson Study Lectures Using the Evaluation of CIPP Models - Jannah, Miftahul (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
This study aims to determine the effectiveness of microteaching integrated lesson study using the CIPP model evaluation (context, input, process, product) which was developed by Daniel Stufflebeam to students of PGMI IAIN Sorong. The method in this study uses a quantitative descriptive approach with a population of all students of PGMI semester VI (six) class of 2019. This sampling uses a saturated sampling technique, where all members are used as a sample population of 27 people. Data were collected by distributing Likert scale questionnaires to respondents. The results showed that the effectiveness of the implementation of integrated microteaching lesson study in all CIPP models was in the very effective category, where for the context model (83%), input (86%), process (89%), and product (88%). This explains that the implementation of microteaching integrated lesson study lectures by students is very effective based on the results of the CIPP model evaluation.